Epidemiology of uraemic itch: New data - Weisshaar, Elke (European journal of pain, 2016)
Chronic itch (CI) is a frequent and impairing symptom in haemodialysis (HD) patients. Within the last decades, worldwide variations were reported in the prevalence of itch in HD patients, ranging from 10 to 77%. Regional differences and especially the irregular pattern of itch in HD may explain why CI is still not well perceived and underestimated in HD patients. The pathogenesis is still unclear and therapy is ineffective in the majority of cases. There is a great diversity of prevalence estimates of itch used in different studies as well, as the study population greatly differs, especially when investigating CI in HD. Due to the demographic situation with a rising number of aged patients and increasing survival rates in HD, the number of HD patients will continuously grow, especially in the Western countries. Up to now, representative epidemiological data on CI in HD were missing. GEHIS (German Epidemiological Hemodialysis Itch Study) was established in 2012 as a representative prospective cross-sectional study. Eight hundred and sixty HD patients from a randomly selected cluster sample were included. The primary outcome measures were different prevalence measures of CI. The point prevalence was 25.2%, the 12-month prevalence was 27.2% and the lifetime prevalence of CI was 35.2%. General health status and health-related quality of life (HRQOl) were significantly impaired in those with CI. Due to the comparability of standards in HD quality, these results can be transferred to Western countries. This study demonstrates that CI is a frequent, long-lasting burden in HD patients affecting every fourth HD patient (point prevalence) and more than every third HD patient at some point in their lifetime.
Article first published 28 September 2015